2017
DOI: 10.1111/rda.12982
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial characteristics in oocytes of the domestic cat (Felis catus) after in vitro maturation and vitrification

Abstract: The objective of this study was to evaluate mitochondria in immature and in vitro-matured domestic cat oocytes and to assess for the first time the effect of vitrification on mitochondrial traits. Mitochondrial distribution and aggregation were assessed using confocal microscopy after staining with the fluorescent dye-MitoTracker Red CMXRos. Only cells at the germinal vesicle and the metaphase II stages of nuclear development, representing immature and mature oocytes, respectively, were included in our study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous studies have recently shown that mitochondria in human oocytes at the GV stage have a heterogeneous distribution but after GVBD this configuration changed rapidly to a homogeneous distribution (Takahashi et al ., 2016). In contrast, cat oocytes either in GV or MII predominantly have mitochondria distributed in the peripheral region (Sowińska et al ., 2017). In sheep, migration of mitochondria to the periphery of the oocyte was observed after 6 h of IVM in COCs from follicles with a diameter of approximately 2 mm (Máximo et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have recently shown that mitochondria in human oocytes at the GV stage have a heterogeneous distribution but after GVBD this configuration changed rapidly to a homogeneous distribution (Takahashi et al ., 2016). In contrast, cat oocytes either in GV or MII predominantly have mitochondria distributed in the peripheral region (Sowińska et al ., 2017). In sheep, migration of mitochondria to the periphery of the oocyte was observed after 6 h of IVM in COCs from follicles with a diameter of approximately 2 mm (Máximo et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…predominantly have mitochondria distributed in the peripheral region (Sowińska et al, 2017). In sheep, migration of mitochondria to the periphery of the oocyte was observed after 6 h of IVM in COCs from follicles with a diameter of approximately 2 mm (Máximo et al, 2012).…”
Section: Effects Of Il1β and Tnfα On Oocyte Maturationmentioning
confidence: 99%
“…In several species and cell types, including gametes, cryopreservation-induced apoptosis has been reported (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In domestic cat immature oocytes, vitrification affects mitochondria aggregation (15), and probably also the permeability of gap junctions hemichannels, causing the loss of small essential metabolites, ionic imbalance, and the penetration of small, potentially toxic, molecules (16). However, information is still limited, and only one study tried to target the apoptosis pathways through an inhibitor of a signaling molecule known as ROCK (Rho-associated coiled-coil containing protein kinase), obtaining an improvement in the developmental competence of VOs in terms of normal fertilization and cleavage rates (4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported for both GV and MII stage domestic cat oocytes that vitrification does not disturb the mitochondrial distribution, but causes mitochondrial aggregation and a decreased fluorescence intensity when evaluated using the MitoTracker Red CMXRos staining (199).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies which investigated the cryopreserved MII oocyte subcellular structures including cortical granules in humans (191)(192)(193)(194)(195), meiotic spindles in mice (194,196,197), mitochondria distribution in humans and domestic cats (195,198,199) and F-actin in humans (108). Our study simultaneously characterized the vitrified-warmed MII mouse oocyte subcellular structures including meiotic spindles, Factin, CGs and mitochondria.…”
Section: Discussionmentioning
confidence: 99%